Space time evolution of the trophic state of a subtropical lagoon: Lagoa da Conceição, Florianópolis Island of Santa Catarina, Brazil - Silva,Victor Eduardo Cury (2017)
ABSTRACT High levels of eutrophication in coastal lagoons due to human activity have been documented worldwide. Among the main impacts observed are anoxia, hypoxia, toxic algal blooms, fish kills, loss of biodiversity and loss of bathing. This study aimed to evaluate the evolution of the trophic state of Lagoa da Conceição, a subtropical lagoon located in an urbanized watershed on the island of Santa Catarina - Brazil. Spatio temporal patterns of stratification and eutrophication were investigated to understand the main biochemical changes over time. The water quality data were obtained from field campaigns supplemented with literature of the last 15 years. The vertical structure of the water column and the trophic state were evaluated by the stratification index and the TRIX index, respectively. Analyses of variance were performed in order to identify possible temporal variations in vertical stratification and trophic level. Eutrophication effects on biogeochemical cycles were verified through a multi-dimensional cluster analysis (MDS) and correlations between variables related to physical, chemical and biological processes were verified by principal component analysis (PCA). The results showed that the water column is homogeneous in all regions except in the central region of the lagoon, and the highest ammonia concentrations and lowest dissolved oxygen concentrations with periods of anoxia are observed in bottom waters. The study looked at the high trophic level of the lagoon and its inability to process the biogeochemical changes imposed by urban development.